Apology for crime: situational analysis of the communication within criminal commands in Brazil (Communication & Society, 2015)
This article presents partial results of my research on strategic violence with political effects in the world of crime in Brazil. Using Situational Analysis as the methodological approach, thirty videos of exaltation of criminal groups and criminal events circulating on YouTube were analyzed. The situational map of the analytic situation empirically constructed allowed the identification of apology for crime as a discursive terrain and a phenomenon of communication with political tones. The description of oneself as member of the armed and political arm of criminal commands, dehumanization of the enemies and affective and cognitive shielding were identified as the axis of a process of preparing for a war around programmatic narratives of commands. The violence against previously named blanks following regimes of practices and conduct programs was identified as the central axis of a programmatic violence suggesting the existence of radicalization processes.